Amphorae in the Eastern Mediterranean - Oniz, Hakan, (Archaeopress Publishing Ltd, 2016)
'Amphorae in the Eastern Mediterranean' is designed to share the subject of amphorae which were found on the Mediterranean coast of Turkey with the wider scholarly community.